Mending a broken heart—the genetics of heart disease - Clark, Natasha; Alibhai, Aziza; Rutland, Catrin Sian (Frontiers Media, 2018)
Heart disease is a major cause of health problems worldwide. There are many different types of heart disease, but one that is fairly common and can have lots of negative side effects is called cardiomyopathy. We know that humans and many mammals, including dogs, get cardiomyopathy. In dilated cardiomyopathy the heart changes shape and often the electrical signals within the heart change. Because of these changes, the heart is not able to pump blood around the body very well, which means that oxygen and nutrients are not delivered to the body at the optimal levels. This can affect day-to-day life, and it can also cause early death. Understanding cardiomyopathy and